A biogenic microbial biosurfactin that degrades difenoconazole fungicide with potential antimicrobial and oil displacement properties. (January 2022) - Satapute, Praveen; Jogaiah, Sudisha
Abstract: Surfactin is a bacterial lipopeptide and an influential biosurfactant mainly known for excellent surfactant ability. The amphiphilic nature of surfactin helps it to sustain under hydrophobic and hydrophilic conditions. In this investigation, a bacterium strain (BTKU3) that produces biosurfactant were isolated from oil-contaminated soil. Based on the blue agar plate (Bap) assay, the BTKU3 strain was found to be promising for biosurfactant production. This strain was later identified as a Lysinibacillus sp. by 16S rRNA sequencing. The characteristics of extracted bacterial surfactin were evidenced by FTIR with the presence of amine, C–H, CO, CC, esters, thiocarbonyl and asymmetric aliphatic C–H stretch molecular structural groups. Further, the extracted bacterial biosurfactant material was subjected to Liquid Chromatography-Mass Spectroscopy (LCMS), and it was identified and confirmed as surfactin with an elution time of 3.1 min and m/z value of 1034. The emulsification and oil displacement tests further proved the surfactin ability with 83% of coconut oil emulsion index and 80 % oil displacement ability with diesel, respectively. Lysinibacillus sp. BTKU3 strain also proved its efficacy in the degradation of difenoconazole by utilizing a capacity of 9.1 μg ml −1 . Thus, it is inferred that the Lysinibacillus sp. BTKU3 strain plays a significant role in the production of surfactin, which positively acts as an antimicrobial agent and reduces contaminants in polluted sites. Highlights: Biosurfactant-producing bacterium ( Lysinibacillus ) was isolated from oil-contaminated soil. Enhanced degradation of difenoconazole fungicide was witnessed by biosurfactin. Biosurfactin also confirms antimicrobial and oil displacement properties. Bacterium carrying biosurfactin can be used in agricultural and environmental applications. Biosurfactin can be introduced as a promising candidate to overcome the increasing pollutants.